Monetary policy pass-through with central bank digital currency - Janet Hua Jiang; Yu Zhu (Bank of Canada, 2021)
This paper investigates how the introduction of an interest-bearing central bank digital currency (CBDC) that serves as a perfect substitute for bank deposits as an electronic means of payment affects monetary policy pass-through. When the deposit market is not fully competitive, the CBDC tends to weaken the pass-through of the interest on reserves. The interest on CBDC impacts the deposit market more directly compared with the interest on reserves. The CBDC rate can also have stronger pass-through to the loan market; however, the effect can be dampened by the policy on the interest on reserves. Therefore, coordination between the two policy rates is needed to effectively achieve policy goals.
Keywords: E50; E52; 330; Digital currencies and fintech; Monetary policy transmission